Answer:
[tex]g=-3[/tex]
Step-by-step explanation:
[tex]3\left(-5-8g\right)+4=61[/tex]
[tex]\mathrm{Subtract\:}4\mathrm{\:from\:both\:sides}[/tex]
[tex]3\left(-5-8g\right)+4-4=61-4[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]3\left(-5-8g\right)=57[/tex]
[tex]\mathrm{Divide\:both\:sides\:by\:}3[/tex]
[tex]\frac{3\left(-5-8g\right)}{3}=\frac{57}{3}[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]-5-8g=19[/tex]
[tex]\mathrm{Add\:}5\mathrm{\:to\:both\:sides}[/tex]
[tex]-5-8g+5=19+5[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]-8g=24[/tex]
[tex]\mathrm{Divide\:both\:sides\:by\:}-8[/tex]
[tex]\frac{-8g}{-8}=\frac{24}{-8}[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]g=-3[/tex]